Critical theories : Indian and western - Sinha M P; Agnihotri, Neeraj (New Delhi Atlantic Publishers, 2013)
Critical theories: Indian and Western presents a reasonably comprehensive account of the basic concepts in Indian and Western literary criticism. The aim of the book is to acquaint the students of M.A. (English literature) with the latest critical theories in the West and their practical application in the analysis and Interpretation of texts. The following authors and critical theories have been discussed: 1. Indian poetics: Bharat, dandin, bhamaha, Vamana, anandavardhana, Abhinavagupta and Karnataka. 2. Greek and Latin criticism: Aristotle, Horace and longinus. 3. Neo-classical criticism: Sidney, Dryden, Pope and Johnson. 4. Nineteenth century criticism: Wordsworth, Coleridge, Shelley and Arnold. 5. Modern British and American criticism: Eliot, Richards, leavis, formalism and Chicago criticism. 6. Contemporary criticism: psycho-analytic criticism, myth criticism, Russian formalism, structuralism/ Post-Structuralism, rezeption-aesthetic, post-colonial theory and feminist criticism. An important aspect of this book is that Sanskrit or Indian poetics has been discussed for the benefit of the students of English literature and so, references to and comparison with Western theories are frequently made. It will be useful for the students and teachers of English literature and researchers in this field.
Keywords: Sociology